2021
DOI: 10.1101/2021.03.18.435920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential responses of amphibians and reptiles to land-use change in the biodiversity hotspot of north-eastern Madagascar

Abstract: Large expanses of tropical rainforest have been converted into agricultural landscapes cultivated by smallholder farmers. This is also the case in north-eastern Madagascar; a region that retains a significant proportions of forest cover despite shifting hill rice cultivation and vanilla agroforestry. The region is also a global hotspot for herpetofauna diversity, but how this diversity is affected by land-use change remains largely unknown. Using a space-for-time study design to uncover land-use effects, we co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…We sampled amphibians and reptiles using repeated time-standardized search walks for 45 min by two observers 91 . We visited each plot both during the day and at night both during the driest (one nocturnal and one diurnal search between October and December 2017; one nocturnal and one diurnal search between August and December 2018) and the wettest period (one nocturnal and one diurnal search between January and April 2018 or in February 2019).…”
Section: Methodsmentioning
confidence: 99%
“…We sampled amphibians and reptiles using repeated time-standardized search walks for 45 min by two observers 91 . We visited each plot both during the day and at night both during the driest (one nocturnal and one diurnal search between October and December 2017; one nocturnal and one diurnal search between August and December 2018) and the wettest period (one nocturnal and one diurnal search between January and April 2018 or in February 2019).…”
Section: Methodsmentioning
confidence: 99%
“…To partly address this problem, working with multiple controls can be useful. For example, by comparing vanilla agroforests in Madagascar with little-used old-growth forest and heavily used forest fragments, Fulgence et al (2021) found that amphibian communities in agroforests are significantly less species rich than those in old-growth forests but comparable to forest fragments; highlighting both opportunities and limitations of amphibian conservation in agroforestry systems.…”
Section: Introductionmentioning
confidence: 99%